An Assessment of the Readability of Recommended Physics Textbooks in Osun State Secondary Schools - Adeyemi, Ademidun Olaitan (2015)
This study examined the readability, relevance, acceptability and appropriateness of recommended Physics textbooks used in Osun State secondary schools. It also determined the extent at which the books complied with approved guidelines for secondary school physics curriculum. These were done with a view to determining the quality and usability of the recommended physics textbooks.